Genome-wide association study identifies key F-box genes linked to ethylene responsiveness and root growth in rice (Oryza sativa L.) - Klinsawang, Suparad; Aesomnuk, Wanchana; Mangkalasane, Piyamongkol; Ruanjaichon, Vinitchan; Siangliw, Jonaliza L.; Pandey, Bipin K.; Bennett, Malcolm J.; Wanchana, Samart; Arikit, Siwaret (Frontiers in Plant Science, 2024)
Rice (Oryza sativa L.) is a staple food for more than half of the world’s population, but its yields are increasingly threatened by environmental problems, including soil compaction. This problem limits root growth which limits water and nutrient foraging capacity thus reduces productivity due to, restricted diffusion of ethylene, a key plant hormone playing an important role in exacerbating these effects. Elevated ethylene levels in compacted soils can further inhibit root development. However, rice varieties that are less sensitive to ethylene may have an advantage as they exhibit better root growth and resource utilization under such conditions. In this study, 220 diverse rice accessions were analyzed to uncover the genetic factors that influence root length reduction (RLR) in response to ethylene. Genome-wide association studies (GWAS) identified a significant QTL on chromosome 10, named qRLR10, associated with ethylene response. Within this region, 20 candidate genes were identified, with three F-box genes namely Os10g0124700, Os10g0126600 and Os10g0128200 showing a strong correlation with RLR variations. These genes are involved in protein degradation, root development and hormone signaling, indicating their possible role in regulating ethylene sensitivity. The results suggest that rice varieties with lower ethylene sensitivity may have better root growth in compacted soils, making them ideal targets for breeding programs aimed at improving resilience to harsh environmental conditions. These results underscore the critical role of ethylene in rice root development and provide valuable insights for future rice improvement strategies aimed at mitigating the effects of soil compaction.